Hydrogen Bonded Nanostructures on Surfaces: STM, XPS and Electrospray Deposition - Swarbrick, Janine Cathy (2006)
Molecules adsorbed on surfaces can show fascinating characteristics and properties. In particular the assembly of molecules into ordered arrays on surfaces is of great interest, whether one considers possible commercial applications or fundamental physical interactions. Specifically, the mediation of ordered molecular arrangements via hydrogen bonding yields many interesting structures.